Protocols Performance in Next Generation Networks - Lykourgiotis, Asimakis; Kotsopoulos, Stavros (Communications - Scientific Letters of the University of Zilina, 2011)
Next Generation Network (NGN) is a packet-based network integrating legacy networks and providing ''anywhere, anytime and on any device'' ubiquitous services. One of the prerequisites of NGN is to support generalized mobility making Mobility Management (MM) a crucial factor towards a seamless provision of multimedia applications. A very promising scenario is the design and implementation of a UMTS / WLAN interworking architecture. In literature a variety of MM protocols operating from different layers of the protocol stack have been proposed. Nevertheless, the comparison of them has been less extensive mainly narrowed between extensions of the same protocol or different basic protocols. In this article a comprehensive comparison between the most efficient approaches of well-known mobility protocols in UMTS/WLAN networks is presented. It is worth noting that the comparison includes not only theoretical but also experimental handoff analysis using OPNET Modeler 15.0 and evaluating the protocols on both non real-time and real-time applications.
Keywords: no keywords